Pengaruh Pengawasan, Komitmen Organisasi, dan Komunikasi Organisasi Terhadap Kinerja Tenaga Kependidikan (Tendik) Pada Universitas Perintis Indonesia - Nofriadi, Nofriadi; Aima, M.Hafidz; Rafky, Rafnelly; Oktarina, Yolanda (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
The problem raised in this research is "Performance of Education Personnel (P of EP) at Indonesian Pioneer University. The variables in this research are the influence of Supervision, Organizational Commitment and Organizational Communication (as independent variables) and the Performance of Education Personnel (as dependent variables). This research pays attention to the level of Education Personnel Performance, supervision, Organizational Commitment and Organizational Communication. This research aims to reveal the influence of Supervision, Organizational Commitment, and Organizational Communication jointly or partially on the Performance of Education Personnel. The conclusion from the research is that partially and simultaneously the variables Supervision, Organizational Commitment and Organizational Communication are proven to have a positive and significant influence on the Performance of Education Personnel, with a contribution of 50.10% with supervision as the most dominant variable. Suggestions: To focus more on improving the Organizational Commitment variable by paying attention to the indicators.